Influence of Different Apical Foramen Morphologies on the Accuracy of Four Electronic Foramen Locators - Furlan, Renan D.; Alcalde, Murilo P.; Vivan, Rodrigo R.; Klymus, Michel E.; Limoeiro, Ana G.S.; Duarte, Marco A.H.; de Vasconcelos, Bruno C. (European Journal of Dentistry, 2024)
Objective The aim of this study was to evaluate the accuracy of the Root ZX II (RZX), Raypex 6 (RAY), EPex Pro (EPEX), and CanalPro (CNP) electronic foramen locators (EFLs) in different foraminal morphologies (fully formed foramen, immature foramen with parallel walls, and immature foramen with divergent walls); this article also evaluated the influence of different penetration levels (0.0 mm and −1.0 mm).Materials and Methods Thirty single-rooted human premolars were accessed and had their cervical/middle thirds prepared with SX ProTaper files. The apical foramens (AF) were standardized to 250 µm and the initial root canal length (RCL1) was measured under 16x magnification with aid of a digital caliper. Using the alginate model, electronic measurements (EM) were taken 1.0 mm up to AF (EM1/-1) and at AF (EM1/0), always using adjusted hand K-files. The root apexes were then cross-sectioned 3.0 mm from the foramen; then, new RCL (RCL2) and electronic measurements were performed (EM2/-1 and EM2/0.0). Finally, retropreparations were performed with instruments SX ProTaper files introduced 4.0 mm in the apicocervical direction. Then new RCL (RCL3) and electronic measurements (EM3/-1 and EM3/0) were performed.Statistical Analysis Values were tabulated and tested for normality using the Shapiro–Wilk test, which yielded nonparametric distributions of the data. Data were subjected to the Kruskal–Wallis and Dunn tests to estimate possible differences between devices as a function of foramen morphology and/or apical limit. The significance level was set at 5.0%.Results In general, the EFLs were accurate in determining the RCL. Statistically significant differences were observed between EPEX and RAY at 0.0, when measuring the divergent AF canals (p < 0.05). Regarding the different foramen morphologies in each EFL, RZX and EPEX showed no interference (p > 0.05), whereas RAY and CNP had lower accuracy levels at 0.0 with divergent AF (p < 0.05).Conclusion The four devices evaluated are accurate to determine the RCL in the conditions tested. The apical limit of penetration did not have significant influence on their accuracy. Conversely, the presence of divergence in the AF walls negatively influenced de RAY and CNP precisions at the foraminal level.
Keywords: electronic foramen locator; endodontic; root canal length